PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT USAHA TERPADU UHAMKA DI JAKARTA SELATAN - Fitri Fadila, Feni; Ludvy, Achmad (Journal of Research and Publication Innovation, 2024)
and work discipline on employee performance at PT Usaha Terpadu UHAMKA South Jakarta. The research method used is descriptive with a quantitative approach with a saturated sample of 88 respondents. The results of this study indicate that X1 (motivation) has a positive but insignificant effect on Y (performance) with a t count of 0.769 <t table. 1.98827. X2 (work discipline) has a positive and significant effect on Y (Performance) with a t count of 10.751> t table 1.98827. X1 (motivation) and X2 (discipline) have a positive and significant effect on y (performance) with an F count of 104.757> F table 3.10. Both variables have a determination strength of 70.5% and the rest is influenced by other variables that are not studied.